Pengaruh Corporate Governance Terhadap Pelaporan Environmental, Social, And Governance (ESG) Pada Perusahaan Sektor Energi Indonesia - Dhea Nabillah Widayanti; Mega Silvia; Emilia Gustini; M. Titan Terzaghi (JURNAL ILMIAH EDUNOMIKA, 2025)
This study investigates the influence of corporate governance elements based on the ASEAN Corporate Governance Scorecard (ACGS) on Environmental, Social, and Governance (ESG) reporting in Indonesian energy sector companies. The research uses five key governance elements: shareholder rights, equitable treatment of shareholders, the role of stakeholders, disclosure and transparency, and board responsibilities. The study focuses on 53 energy companies listed on the Indonesia Stock Exchange for the period 2022–2023. A quantitative approach was applied, using content analysis to assess ESG reporting quality based on the indicators from the Indonesian Ministry of Finance. The results aim to identify which governance components most significantly impact ESG disclosure practices. The findings are expected to offer insights for regulators, investors, and companies in enhancing governance standards and sustainability practices, particularly in environmentally critical sectors like energy. Keywords : corporate governance, ASEAN Corporate Governance Scorecard, ESG reporting, sustainability, energy sector